Uncovering the Genomic Landscape in Newly Diagnosed and Relapsed Pediatric Cytogenetically Normal FLT3‐ITD AML. Issue 6 (20th August 2019) - Buelow, Daelynn R.; Pounds, Stanley B.; Wang, Yong‐Dong; Shi, Lei; Li, Yongjin; Finkelstein, David; Shurtleff, Sheila; Neale, Geoffrey; Inaba, Hiroto; Ribeiro, Raul C.; Palumbo, Reid; Garrison, Dominique; et al.
Abstract : Fms‐like tyrosine kinase 3 ( FLT3 ) internal tandem duplication (ITD) mutations, common in pediatric acute myeloid leukemia (AML), associate with early relapse and poor prognosis. Past studies have suggested additional cooperative mutations are required for leukemogenesis in FLT3 ‐ITD+ AML. Using RNA sequencing and a next‐generation targeted gene panel, we broadly characterize the co‐occurring genomic alterations in pediatric cytogenetically normal (CN) FLT3 ‐ITD+ AML to gain a deeper understanding of the clonal patterns and heterogeneity at diagnosis and relapse. We show that chimeric transcripts were present in 21 of 34 (62%) of de novo samples, 2 (6%) of these samples included a rare reoccurring fusion partner BCL11B . At diagnosis, the median number of mutations other than FLT3 per patient was 1 (range 0–3), which involved 8 gene pathways; WT1 and NPM1 mutations were frequently observed (35% and 24%, respectively). Fusion transcripts and high variant allele frequency (VAF) mutants, which included WT1, NPM1, SMARCA2, RAD21, and TYK2, were retained from diagnosis to relapse. We did observe reduction in VAF of simple or single mutation clones, but VAFs were preserved or expanded in more complex clones with multiple mutations. Our data provide the first insight into the genomic complexity of pediatric CN FLT3 ‐ITD+ AML and could help stratify future targeted treatment strategies.